An Ethnosains Based Project Based Learning Model with Flipped Classroom on Creative Thinking Skills - Rina Rahayu; Sutikno; Dyah Rini Indriyanti (Jurnal Penelitian Pendidikan IPA, 2023)
Education in the 21st century demands very rapid development of knowledge and technology, so that 4C skills are needed, namely creative thinking skills, critical thinking and problem solving, communicating, and collaborating to face global challenges. Creative thinking skills as a very important skill for students in the era of global competition because the level of complexity of problems in all aspects of modern life is also getting higher. Learning with ethnoscience can be implemented in the PjBL learning model by incorporating the culture that develops in society into learning. Flipped Classroom is carried out by students by studying at home through books or videos that have been integrated with the culture of society. This study aims to determine the effect of the ethnoscience-based PjBL learning model with a flipped classroom on creative thinking skills. This research is a literature study using secondary data sources in the form of books and scientific journal articles. Data was collected using publish or perish applications and analyzed one by one manually. The results show that the application of project-based models and ethnoscience with flipped classrooms influences creative thinking skills.